Management of A Preeclampsia Patient with Diabetic Ketoacidosis and Acute Pulmonary Edema : A Case Report - Pison , Osmond Muftilov; Fransisca, Arna (Journal of Society Medicine, 2025)
Introduction: Preeclampsia is a hypertensive disorder that develops after 20 weeks of gestation, often accompanied by proteinuria and maternal organ dysfunction, including pulmonary edema. Women with diabetes are at a higher risk for developing preeclampsia and its complications. Managing severe preeclampsia requires prompt monitoring and intervention, particularly when organ failure and metabolic disturbances are present. Case Report: A 25-year-old pregnant woman at 30-31 weeks of gestation presented with severe dyspnea, high blood pressure (185/105 mmHg), and metabolic disturbances, including diabetic ketoacidosis (DKA) and pulmonary edema. The patient had no prior history of hypertension or diabetes. Laboratory tests revealed elevated ketones, hyponatremia, and mild proteinuria. She was admitted to the ICU, where she received nitroglycerin infusion, fluid resuscitation, and blood glucose regulation. However, her condition worsened, and she required intubation and mechanical ventilation due to severe hypoxemia and respiratory failure. After stabilization, a cesarean section was performed, leading to improvements in her condition. The patient was extubated after three days, and her blood glucose levels were stabilized. Conclusion: This case highlights the complexities of managing severe preeclampsia complicated by pulmonary edema, diabetic ketoacidosis, and urinary tract infections. Early recognition, aggressive treatment, and multidisciplinary care are essential for improving outcomes and preventing further complications in high-risk pregnancies.